Removal Of Dissolved Cadmium Ions from Contaminated Wastewater using Raw Scrap Zero-Valent Iron And Zero Valent Aluminum as Locally Available and Inexpensive Sorbent Wastes - M. Rashid, Hayder; A.H. Faisal, Ayad (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
The current study was to examine the reliability and effectiveness of using most abundant, inexpensive waste in the form of scrap raw zero valent aluminum ZVAI and zero valent iron ZVI for the capture, retard, and removal of one of the most serious and hazardous heavy metals cadmium dissolved in water. Batch tests were conducted to examine contact time (0-250) min, sorbent dose (0.25-1 g ZVAI/100 mL and 2-8 g ZVI/100 mL), initial pH (3-6), pollutant concentration of 50mg/L initially, and speed of agitation (0-250) rpm . Maximum contaminant removal efficiency corresponding to (90 %) for cadmium at 250 min contact time, 1g ZVAI/ 6g ZVI sorbent mass ratio, pH 5.5, pollutant concentration of 50 mg/L initially, and 250 rpm agitation speed were obtained. Langmuir and Freundlich isotherms were presumed to fit the batch kinetics data for the sorption of Cd(II) onto ZVAI and/or ZVI and found that Langmuir (I) was the most representative model type with coefficient of determination R2 greater than 0.9115. Kinetics data for the sorption of Cd(II) onto ZVAI/ZVI mixture and due to the good agreement between the fitted and the experimental results; the data was found to obey the pseudo second order model. The scanning electron microscopy (SEM) for the ZVI and ZVAI was conducted before and after the sorbent-liquid reaction and revealed distinct morphological changes in the sorbent surface due to the contaminant saturation and pore channel blockages that ceased the sorption process.